Peculiarities of Clinical Course Without Several Form of Epileptic Encephalopathy in Preschool Children (Texas Journal of Medical Science, 2022)
Epileptic encephalopathy is a condition when a pathological altered brain electrogenesis is the cause of impaired brain function [5,6]. The epileptic process leads to progressive impairment of brain functions. According to the literature, these disorders depend on the form of 5 to 40% of behavioral, mental and neuropsychological disorders [2,4,8,9]. Currently, some researchers consider interictal epileptic psychoses as a manifestation of epileptic encephalopathy. Epileptic encephalopathy is a condition where pathologically altered brain electrogenesis is the cause of brain dysfunctions. In which the epileptic process as such leads to progressive dysfunctions of the brain.